VISUAL METAMORPHOSES: A CULTURAL ANALYSIS OF DIGITAL CYBERAESTHETICS / ВИЗУАЛЬНЫЕ МЕТАМОРФОЗЫ: КУЛЬТУРОЛОГИЧЕСКИЙ АНАЛИЗ ЦИФРОВОЙ КИБЕРЭСТЕТИКИ - ZABELINA MARIIA V. / ЗАБЕЛИНА М.В. (Наука телевидения, 2024)
This article focuses on the emerging styles of visual digital aesthetics that have become relevant in light of technological advancements and the introduction of innovative tools for creating and processing digital images. The analysis is based on a cultural approach and aims to identify the influence of contemporary digital technologies on the shaping of cultural benchmarks and aesthetic preferences in art and design. The primary focus is on scrutinizing the defining attributes of modern styles that have taken shape within the digital sphere at the onset of the 21st century (such as vaporwave, seapunk, webpunk, psychedelia, pixel art, voxel art, and others) and delving into their artistic autonomy and cultural nuances. Style is defined here as both a guiding principle of artistic thought and a distinctive mode of communication among cultural agents. An integral component of this study involves comprehending how digital technologies impact the interpretation of contemporary culture and society at large. The study aims to uncover the peculiarities of modern transnational culture, as a mode of consciousness and worldview, through the lens of the artistic culture of the early 21st century. The research identifies overarching tendencies characteristic of contemporary network art, outlining the interrelations and differentiations among new digital styles. It meticulously examines distinct style clusters based on various criteria. The classification of contemporary visual styles is predicated on methods and techniques of creation and imitation, usage contexts, presentation specifics, and design elements. The results of the study can enrich the exploration of contemporary culture and visual phenomena, aiding in forecasting future trajectories within the realm of innovative visual expressions. Статья посвящена новым стилям визуальной цифровой эстетики, ставшим актуальными в свете развития технологий и возникновения новых средств для создания и обработки цифровых изображений. Анализ основан на культурологическом подходе и направлен на выявление влияния современных цифровых технологий на формирование культурных ориентиров и эстетических предпочтений в искусстве и дизайне. Основное внимание уделяется исследованию характеристик современных стилей, сформировавшихся в цифровой среде на рубеже XXI века (среди них Vaporwave, Sea punk, Web punk, Psychedelica, пиксель-арт, воксель-арт др.), их художественной самости и культурным особенностям. Стиль в данном случае определяется как принцип художественного мышления и особая форма коммуникации субъектов культуры. Важной частью исследования является понимание того, как цифровые технологии воздействуют на интерпретацию современной культуры и общества в целом. Выявляются особенности современной транснациональной культуры (как типа сознания и картины мира) через призму художественной культуры первой четверти XXI века. В работе обозначены общие тенденции, характерные для современного сетевого искусства, представлены взаимосвязи и отличия новых цифровых стилей, а также детально рассмотрены отдельные объединения стилей по различным критериям. Классификация современных визуальных стилей базируется на методах и техниках создания и имитации, контексте использования, особенностях презентации, дизайнерских элементах. Полученные результаты могут быть применены для углубленного анализа современной культуры и визуальных явлений, а также для прогнозирования будущих направлений развития в области нового визуального.